Protective effects of Equisetum arvense methanolic extract on sperm characteristics and in vitro fertilization potential in experimental diabetic mice: An experimental study - Mehrsa Fajri; Abbas Ahmadi; Rajabali Sadrkhanlou (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Diabetes mellitus is a metabolic disorder characterized by impaired insulin secretion or the inability of tissues to respond to insulin. This disease can damage the testis and reduce semen quality. Therefore, it can impair the potential for male fertility. Different herbal therapeutic treatments have been used to control diabetes and its complications.Objective: This study aimed to evaluate the effects of streptozotocin-induced diabetes on sperm and in vitro fertilization (IVF) potential and investigate the protective effects of Equisetum arvense methanolic extract on diabetic mice.Materials and Methods: Twenty-four adult male mice were divided into four groups: control-sham, diabetic, diabetic + Equisetum extract (250 mg/kg), and diabetic + Equisetum extract (500 mg/kg). After 45 days, sperm samples were collected from the cauda epididymis to evaluate the characteristics of sperm (including viability, count, motility, morphology and chromatin/DNA integrity of sperm) and the IVF potential.Results: Sperm motility and viability were increased remarkably (p ≤ 0.001) in the treated groups compared with the non-treated diabetic group. The decrease in sperm count in the diabetic group compared with the treated groups was not significant. Moreover, the percentage of sperm with DNA damage, nuclear immaturity, and abnormal morphology was decreased significantly (p ≤ 0.001) in the treated groups compared with the diabetic group. The treated animals exhibited remarkably higher fertilization rates and a higher percentage of fertilized oocytes that developed toward the blastocyst stage compared with the non-treated diabetic group (p ≤ 0.001).Conclusion: The methanolic extract of the Equisetum arvense inhibited diabetes-induced detrimental effects on sperm quality and fertilization rate, which may have been associated with hypoglycemic and antioxidative activities in this plant.